Rate of natural predation of Anagasta kuehniella eggs at different plant compositions (Nucleus, 2019)
The parasitoid Trichogramma spp. multiplied in moth eggs Anagasta kuehniella may be released by the technique of spreading the eggs unprotected, but natural predation can be an impediment to this procedure. This study aimed to assess the rhythm of natural predation of A. kuehniella eggs in different vegetation compositions at Moura Lacerda University Center, Ribeirão Preto, Brazil. Three agricultural crops (coffee, sugarcane and pasture), three orchards of fruit trees (mango, lemon and banana) and three thickets were selected. Blue cardboards of 5 x 5 cm were painted with a thin layer of 50% gum arabic and then eggs of A. kuehniella were spread evenly over the same. Between 2013, October 14th and 19th, 10 cards were distributed in each area mentioned, under the ground, except in orchards, where 5 were fixed in plants and the other 5 placed in the ground, leaving about 1 m from each other. The cards were placed in the field at 6:00 am and changed every two hours to 18:00 pm. A night evaluation from 18:00 pm to 6:00 am was also performed. There were significant differences among treatments, with a higher average percentage of predation in coffee, sugarcane crop, lemon, banana and thicket areas from landmark and hill of the campus than that in pasture, mango orchard and the lakeside thicket. Predation was more intense from 8:00 to 10:00 am, from 12:00 to 16:00 pm, in general, and in the evening for the most of the vegetables compositions studied.